Stefania Landi, "Grain silos from the thirties in Italy. Analysis, conservation and adaptive reuse", Pisa University Press, Pisa 2021, 291 p. - Roberto Parisi, recensione di (OS. Opificio della Storia, 2023)
Stefania Landi, "Grain silos from the thirties in Italy. Analysis, conservation and adaptive reuse", Pisa University Press, Pisa 2021, 291 p.